Noninvasive Vascular Diagnosis : A Practical Textbook for Clinicians - AbuRahma, Ali F. (Springer International Publishing : Imprint: Springer, 2017)
This revised and updated edition reflects the increasing popularity of noninvasive techniques in the management of vascular disease. It represents the definitive text written on the subject and has been honed over the past editions to represent the enormous number of changes to the use of imaging to diagnose the multitude of conditions being seen in the clinic and surgical suite. Noninvasive Vascular Diagnosis comprehensively covers all aspects of noninvasive evaluation of the circulatory system, including the extremities, cerebrovascular, and abdomen. It is well supported by exceptional illustrative material, making it invaluable to all those who work in vascular laboratories as well as internists, cardiologists, radiologists, vascular surgeons, vascular medicine specialists, vascular laboratory directors and staff, general surgeons involved in vascular surgery and the vascular surgery community in general.
Keywords: Medicine.; Internal medicine.; Cardiac surgery.; Vascular surgery.; elektronické knihy; electronic books